Assessment of explosive force in the performance of high school students (RIAF. International Journal of Physical Activity, 2024)
The main objective of this article is to evaluate explosive force in sports training and to analyze the performance of high school students in the "Santa Catalina Labouré" Fiscal Educational Unit. To fulfill this purpose, it uses a descriptive methodology, 20 students were selected with an intentional sampling by criterion from a total population of 110, following specific inclusion criteria such as ages between 16-17 years, male and female, students of first, second and third Unified General Baccalaureate (BGU). The results reveal that, in the group of male students, the distance varied between 52.4 cm and 62.1 cm, both above average. For female students, distances ranged from 42.6 cm to 53.5 cm. Most students have exceeded the average of 54.1 cm in the vertical jump, which suggests good physical condition in general.
Keywords: Physical Ability; strength; Sports training; Sargent test; assessment